Dance Upon the Air - Roberts, Nora (London Piatkus, 2008)
When Nell Channing arrives on Three Sisters Island, she hopes she has finally found refuge from her abusive husband. But even in this peaceful place, she feels haunted by fear. Then she discovers the island is suffering under a terrible curse and that she must find the power to save herself.
Keywords: Massachusetts -- Witches